Lucifer Over Luxor: Archaeology, Egyptology, and Occultism in Kenneth Anger's Magick Lantern Cycle. Issue 1 (29th April 2016) - Doyle White, Ethan
One of the great figureheads of American experimental cinema, Kenneth Anger (b.1927), is internationally renowned for his pioneering work, recognisable for its blend of homoerotica, popular and classical music, and dark, symbolist imagery. A follower of Thelema, the religion of infamous British occultist Aleister Crowley (1875–1947), Anger's work is imbued with occult themes and undercurrents rarely comprehensible to the non-initiated viewer. In exploring these esoteric ideas, Anger makes use of archaeology and heritage in his short films Eaux d'Artifice (1953) and Inauguration of the Pleasure Dome (1954–66), as well as in the lost films The Love That Whirls (1949) and Thelema Abbey (1955), which utilize such disparate elements as Aztec human sacrifice and putative Renaissance Satanism. However, this theme only reaches its apex in Lucifer Rising (1980), an exploration of Thelemic theology filmed at such sites as Avebury, Luxor, and Karnak, which reflects and propagates the Thelemic view of the past—an 'alternative archaeology' rooted in Crowley's own fascination with Egyptomania. This paper seeks to explore Anger's use of the past and place it in its proper context of twentieth-century Western esotericism.